Prevalence of qacE AND qacE[delta]1 resistance genes in pseudomonas species isolates from hospitals in Benin City, Nigeria - Felix. A. Okunrobo; Helen. O Ogefere; Richard Omoregie (Publication Department, Universitas Warmadewa, 2025)
Background: The multi-drug efflux pump systems play a significant role in the mechanism of resistance to biocides in Pseudomonas species. This bacterium has been shown to harbor multi-drug transporter efflux systems genes involving QacE and QacE[delta]l, as do other gram negative bacteria. In Nigeria, the use of antimicrobial agents is unregulated, particularly the use of biocidal formulations both in health care facilities and for domestic purposes. Due to paucity of data on the distribution of qac genes in the health-care environment in Nigeria, this study aimed to determine the distribution of qacE and qacE[delta]1 genes among Pseudomonads–both aeruginosa and non-aeruginosa isolates, from clinical and environmental sources within hospitals in Benin City. Method: A total of 1200 specimens consisting of 500 clinical (wound, urine, ear swabs, high vaginal and endo-cervical swabs, eye swabs, aspirates, catheter tips, sputum and throat swabs) and 700 environmental (sinks, floors and bench tops) were used for this study. All specimens were processed to recover Pseudomonads using cetrimide agar. The isolates were identified with biochemical tests and 16S rRNA. The presence of qacE and qacE[delta]1 genes was detected by PCR (polymerase chain reaction). Result: Pseudomonas aeruginosa and non-aeruginosa isolates were recovered mostly from sinks and wounds. The prevalence of qacE and qacE[delta]1 genes did not differ significantly (p>0.05) between P. aeruginosa and their non-aeruginosa counterparts in both clinical and environmental isolates. In conclusion, we highlight the prevalence of qacE and qacE[delta]1 resistance genes in varying proportions among clinical and environmental pseudomonas species isolates in hospitals in Benin city, Nigeria